SCORE2-Diabetes and Cardiovascular Risk: Insights from Traditional and Non-Traditional Biomarkers - Klisic, Aleksandra; Babovic, Batric; Milinkovic, Neda; Karakasis, Paschalis; Mercantepe, Filiz (Journal of Medical Biochemistry, 2026)
Background: Cardiovascular (CV) disease is the major cause of death in type 2 diabetes mellitus (T2DM). The SCORE2-Diabetes is a recently developed algorithm that improves CV risk assessment in patients with T2DM. The aim of the study was to explore the relationship between SCORE2-Diabetes and clinical and biochemical parameters in individuals with T2DM. Methods: A total of 106 T2DM patients were evaluated in this cross-sectional study. SCORE2-Diabetes (%) was calculated, and associations with clinical and biochemical parameters were analyzed using correlation and logistic regression analysis. Results: In multivariate logistic regression analysis, retinol-binding protein 4 (RBP4) (OR 1.08, 95% CI 1.03–1.13, p=0.001), urinary albumin excretion (UAE) (OR 1.01, 95% CI 1.00–1.01, p=0.023), and triglycerides (TG) (OR 2.91, 95% CI 1.12–7.57, p=0.028) were independently correlated with SCORE2-Diabetes. ROC analysis showed high diagnostic accuracy for UAE (AUC=0.894) and RBP4 (AUC=0.871), while TG showed moderate accuracy (AUC=0.713) for identifying patients with high cardiovascular risk according to the SCORE2-Diabetes. Conclusions: Elevated RBP4 and UAE are independently associated increased SCORE2-Diabetes risk. Incorporation of these biomarkers might refine cardiovascular risk stratification in T2DM, and enable early intervention. Prospective studies are needed to confirm such results and assess therapeutic implications.